Characteristics of the Interface between Bamboo Grids and Reinforced Soil of High-Filled Embankments in Loess Areas - Jingwei Zhang; Jia Li; Julong Wang; Shuaiqi Xu (Advances in Civil Engineering)
There are a large number of high-filled and deep-dug highways in loess areas. The differential settlement between the filled and undisturbed soils is the main cause of damage. Bamboo grids are good reinforcement and flexural tensile materials for highway subgrades, and the properties of the interface between the bamboo grid and loess soil affect the safety and stability of embankments. First, the feasibility of bamboo grid application in high-filled embankments in loess areas was verified based on a durability analysis and test of the mechanical properties of bamboo. Then, a series of large-scale direct shear tests were carried out to determine the shear properties of the interface between bamboo grids and loess soils. The influential factors of vertical stress, shear rate, grid spacing, and compactness on the shear properties were studied, and the related mechanism was discussed. The results show that bamboo grids enhance the shear strength of loess soils more than geogrids under different vertical stresses because of the passive friction resistance between the vertical and horizontal ribs and soil particles, the bite force of particle skeletons, and the surface friction of grids. Bamboo grids enhance the stability and shear resistance of soils because of their good deformation performance, and thus, the shear rate effect within 7 mm/min can be negligible. The greater the relative compaction of the subgrade soil, the better the reinforcement effect owing to the greater cohesive force, greater internal friction angle, and better bite force. The variation in grid spacing changes the embedded effect of soil, side friction resistance, and size of the contact area. The shear resistance has an optimal value, which first increases and then decreases. Therefore, in practical applications, it is necessary to test the optimal bamboo grid spacing for a project.